Lippincott's guide to infectious diseases (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2012)
"Compliant with CDC and WHO guidelines, this new A-to-Z reference provides an overview of 160 infectious diseases, from the common cold and otitis media to MRSA and other newer threats, including Bartonella quintana"